Gambaran Kemampuan Keuangan Provinsi Di Wilayah Barat Indonesia dan Kebijakan pada Transfer Ke Daerah Tahun 2010-2020 - Rendy Alvaro (Pusat Kajian Anggaran, 2022)
This study aims to provide an overview of the regional financial capacity in the western provinces of Indonesia. Furthermore, based on these results, recommendations can be given regarding steps that can be taken by the government regarding transfer policies to the regions. This research uses share and growth analysis and the quadrant method. Based on the results of the share analysis, five provinces with the highest share values were obtained, namely Riau, Riau Islands, Banten, Bali Province, and South Sumatra Province. Using growth analysis, there are five provinces with the highest growth values, namely Banten, Bali, DI Yogyakarta, Bengkulu, and Bangka Belitung. By using the quadrant method, there are two regions in quadrant I, two regions in quadrant II, five regions in quadrant III, and seven regions in quadrant IV.